2001
DOI: 10.1089/10507250152484547
|View full text |Cite
|
Sign up to set email alerts
|

Topical Triiodothyronine Stimulates Epidermal Proliferation, Dermal Thickening, and Hair Growth in Mice and Rats

Abstract: The skin is a classic target tissue for thyroid hormone action. Although the histology of skin in hypothyroid states is well documented, the literature contains little assessment of skin in thyrotoxic states. In light of the paucity of information on skin under the influence of excess thyroid hormone, we investigated the direct effect of thyroid hormone on skin. Triiodothyronine (T3) was applied topically daily in liposomes to SKH-1 hairless mice for 7 days and to CD rats for 2 weeks. There was a dose-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
4
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 26 publications
10
68
4
1
Order By: Relevance
“…However, our results show that skin proliferation was similarly reduced in KO and hypothyroid mice, indicating that receptor loss is equivalent to ligand loss in this tissue and that therefore thyroid hormone binding to TRs rather than the effect of the corepressor-bound receptors mediates their actions on skin proliferation. These results are in agreement with the previous observation that topical application of the thyroid hormone triiodothyronine stimulates epidermal proliferation in rodents (30). On the other hand, distinct phenotypes are found in mice in which TR␣1 or TR␤ (9, 10) are individually deleted, and when both genes are inactivated, an array of phenotypes, not found in the single receptor-deficient mice, are observed (11), indicating that TR␣1 and TR␤ can substitute for each other to mediate some actions of the thyroid hormones, but they can also mediate isoform-specific functions (54).…”
Section: Discussionsupporting
confidence: 93%
“…However, our results show that skin proliferation was similarly reduced in KO and hypothyroid mice, indicating that receptor loss is equivalent to ligand loss in this tissue and that therefore thyroid hormone binding to TRs rather than the effect of the corepressor-bound receptors mediates their actions on skin proliferation. These results are in agreement with the previous observation that topical application of the thyroid hormone triiodothyronine stimulates epidermal proliferation in rodents (30). On the other hand, distinct phenotypes are found in mice in which TR␣1 or TR␤ (9, 10) are individually deleted, and when both genes are inactivated, an array of phenotypes, not found in the single receptor-deficient mice, are observed (11), indicating that TR␣1 and TR␤ can substitute for each other to mediate some actions of the thyroid hormones, but they can also mediate isoform-specific functions (54).…”
Section: Discussionsupporting
confidence: 93%
“…In vitro, T3 stimulates keratinocyte proliferation. In vivo, topical T3 stimulates epidermal proliferation, dermal thickening and hair growth (Safer et al, 2001;Safer et al, 2003;Safer, 2005). Topical triac (tri-iodothyroacetic acid) thickens skin by stimulating the production of collagen (Faergemann et al, 2002;Yazdanparast et al, 2004).…”
Section: Function Of Ths In Development and Homeostasismentioning
confidence: 99%
“…First, hypothyroidism is associated with retarded wound repair probably through decreasing collagen synthesis and or keratinocyte proliferation [21,23,24] which is reversible with thyroid hormone replacement [21,25]. Second, in vitro and in vivo studies have designated that thyroid hormones stimulate keratinocyte and epidermal proliferation as well as hair growth [20,21,26]. Finally, it has been shown that daily treatment with 150 ng topical T3 in mice improves wound closure significantly [19].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from stimulation of keratinocytes proliferation [21,26], T3 may exert positive effects on wound healing by increasing the circulation to the site of injury through vasodilation [29,30]. Another interesting contributing mechanism may be the potential antiseptic action of thyroid hormones [31,32].…”
Section: Discussionmentioning
confidence: 99%